2004
DOI: 10.1002/tox.20012
|View full text |Cite
|
Sign up to set email alerts
|

Xenoestrogenic effects of ethinylestradiol in zebrafish (Danio rerio)

Abstract: To assess the estrogenic effects of ethinylestradiol on zebrafish, zebrafish at different developmental stages (embryos, juveniles, and adults) were exposed to the synthetic hormone ethinylestradiol (EE2) in concentrations of 1, 10, and 100 ng/L for up to 33 days. Survival, hatching, length, weight, growth, condition, hepatosomatic index, gonadosomatic index, and vitellogenin (VTG) production were examined. Exposure of zebrafish juveniles and embryos to 100 ng EE2/L for up to 33 days had significant effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 45 publications
5
28
0
Order By: Relevance
“…There was no change in levels of expression between treatment or timepoints in the female fish. In the male fish there was no significant difference in expression between the control and the QUIN group, however the males exposed to EE 2 demonstrated significantly higher levels of expression, which is consistent with results from other studies (Versonnen & Janssen, 2004).…”
Section: Estrogenicitysupporting
confidence: 91%
See 2 more Smart Citations
“…There was no change in levels of expression between treatment or timepoints in the female fish. In the male fish there was no significant difference in expression between the control and the QUIN group, however the males exposed to EE 2 demonstrated significantly higher levels of expression, which is consistent with results from other studies (Versonnen & Janssen, 2004).…”
Section: Estrogenicitysupporting
confidence: 91%
“…The effect of EE 2 exposure on fish fecundity has been well documented (Rahman, Yanful, & Jasim, 2009;Segner et al, 2003). EE 2 exposure results in reduced ovary size, altered gonadal structure ( Van den Belt, et al, 2002;Versonnen & Janssen, 2004) and a decline in expression of genes involved in the follicular recruitment and steroidogenesis, maturation and ovulation pathways (Carnevali et al, 2010;Urbatzka et al, 2012;Van den Belt et al, 2001). …”
Section: Thesis Objectives and Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…Animals exposed to environmental estrogens have exhibited defects in sexual development, sexual behavior, and reproduction organ malformation (Blomqvist et al 2006, Furuya et al 2006, Ma & Sassoon 2006. Besides these effects, fishes display abnormal intersexuality, reduced spawning success, reduced female fecundity, delayed male gonadal differentiation, reproductive duct malformation, and complete sex reversal (Jobling et al 1998, Scholz & Gutzeit 2000, Van den Belt et al 2001, Balch et al 2004, Nash et al 2004, Versonnen & Janssen 2004, Mills & Chichester 2005, Campbell et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, laboratory-based studies have shown that some environmental oestrogens not only affect reproduction of fish but can also impact on other endocrinemediated processes, including somatic growth (e.g. 17a-ethinyloestradiol (EE 2 ; Versonnen & Janssen 2004, Van den Belt et al 2003, 4-tert-nonylphenol (NP; Dreze et al 2000, Magliulo et al 2002, methoxychlor (Magliulo et al 2002)), osmoregulation (e.g. 17b-oestradiol (E 2 ) and NP (Madsen et al 1997, Vijayan et al 2001, Arsenault et al 2004, Madsen et al 2004, McCormick et al 2005), immune function (e.g.…”
Section: Introductionmentioning
confidence: 99%